HHUBUNGAN ANTARA IKLIM ORGANISASI SEKOLAH DENGAN MOTIVASI KERJA GURU DI SEKOLAH MENENGAH PERTAMA - Zulfa Awaliyah Darajat; Lulu Alwiyah; Dewi Cahyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the relationship between school organizational climate and teachers’ work motivation at the junior secondary school level. Organizational climate refers to teachers' collective perceptions of the school work environment, while work motivation relates to internal and external factors that influence teachers' enthusiasm and performance in carrying out teaching duties. The research method used is a quantitative approach with a correlational type. Data collection was carried out using a closed-ended questionnaire based on a Likert scale. The sample consisted of 17 teachers from SMP AL-ISHLAH in Tasikmalaya Regency. Data analysis was conducted using the Kolmogorov–Smirnov normality test and Pearson Product Moment correlation test. The results showed a very strong and significant relationship between the school’s organizational climate and teachers’ work motivation. The correlation coefficient obtained was r = 0.944 with a significance value of p = 0.0047. This finding indicates that the more positive the school organizational climate perceived by teachers, the higher their work motivation. This research highlights the importance of creating a supportive and motivating work environment in school management.